Systematic evaluation of CrRNA design parameters for optimized Cas13d-mediated RNA targeting in chicken cells - Emily Hann; Debolina Majumdar; Daniel Layton; Mohamed Fareh; David M. Cahill; Mark Ziemann; Beata Ujvari; Karel A. Schat; Arjun Challagulla (Functional & Integrative Genomics, 2025)
The CRISPR-Cas13 system has emerged as a powerful platform for programmable RNA targeting, offering efficient and sequence-specific silencing of coding and non-coding transcripts. The RNA-targeting capabilities of CRISPR-Cas13 have been harnessed to silence transcripts harbouring pathogenic mutations and combat infectious diseases. However, the molecular basis of on-target and collateral activity are not completely understood, limiting the utility of Cas13 systems. In this study, we delineate the principles for the development of effective crRNAs by targeting DsRed fluorescence reporter and synthetic influenza mRNA in chicken fibroblast DF1 cells. To systematically determine the optimal design for RfxCas13d crRNA, we investigated the minimum length of the crRNA, importance of protospacer flanking sequence, degree of mismatch tolerance, and off target effects. Our data reveal variable knockdown levels between crRNAs, in which several crRNAs achieved over 95% target knockdown. We show that crRNAs exhibit a high degree of tolerance to single-nucleotide mismatches, regardless of their position in the spacer sequence. However, 4-nt mismatches between the spacer and the target significantly reduces targeting efficacy, whereas eight nucleotide mismatches completely abolish the activity of RfxCas13d. Finally, we compared targeting efficiency and collateral activity of two widely used RfxCas13d and HfCas13d variants. Our data extend current understanding of Cas13d-mediated RNA targeting and offer a framework for rational crRNA design to enhance effectiveness in diverse applications, including antiviral strategies.

Genetic strategies for avian influenza resilience in poultry: from host-pathogen interaction studies to precision breeding - Debolina Majumdar; Emily Hann; Kirsty R. Short; Karel A. Schat; Arjun Challagulla (Functional & Integrative Genomics, 2025)
Avian influenza virus (AIV) remains a persistent threat to global poultry production and public health, owing to its ability to infect a wide range of avian and mammalian species. The global resurgence of H5N1 and the limitations associated with control measures in intensive poultry production have highlighted the need for a paradigm shift in disease management strategies. In this context, the development of AIV resilient poultry lines is gaining momentum as a promising strategy for long-term disease management. In this review, we discuss the ongoing threat of AIV to poultry production and explore genetic approaches to enhance resilience against avian influenza. We primarily focus on intracellular host restriction factors that inhibit viral replication, followed by an overview of virus-targeted strategies. We further discuss the use of genome-wide screening approaches to study host–pathogen interactions to identify high confidence host targets. Finally, we highlight studies that develop transgenic, or genome engineered chickens with the aim to enhance AIV resilience and their potential for transforming AIV control in poultry production.

Potential benefits of gene editing for the future of poultry farming - Mark L. Tizard; Kristie A. Jenkins; Caitlin A. Cooper; Mark E. Woodcock; Arjun Challagulla; Timothy J. Doran (Transgenic Research, 2019)

Generation of gene edited birds in one generation using sperm transfection assisted gene editing (STAGE) - Caitlin A. Cooper; Arjun Challagulla; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Kirsten R. Morris; Mark L. Tizard; Timothy J. Doran (Transgenic Research, 2017)